2022
DOI: 10.48550/arxiv.2205.13273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemia Detection Using Hypercomplex-Valued Convolutional Neural Networks

Abstract: This paper features convolutional neural networks defined on hypercomplex algebras applied to classify lymphocytes in blood smear digital microscopic images. Such classification is helpful for the diagnosis of acute lymphoblast leukemia (ALL), a type of blood cancer. We perform the classification task using eight hypercomplex-valued convolutional neural networks (HvCNNs) along with real-valued convolutional networks. Our results show that HvCNNs perform better than the real-valued model, showcasing higher accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It was observed that diagnosis of acute leukaemia has generated a lot of attention and many scholars have employed deep neural networks for the same. The use of hypercomplex-valued network (HVN) was investigated by Vieira and Vale [38], using 8 complex-valued CNN. Analysis showed that their proposed hypercomplex CNN produced commendable results at 96.6% when tested on ALL-IDB2 dataset using 50% of the data for texting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was observed that diagnosis of acute leukaemia has generated a lot of attention and many scholars have employed deep neural networks for the same. The use of hypercomplex-valued network (HVN) was investigated by Vieira and Vale [38], using 8 complex-valued CNN. Analysis showed that their proposed hypercomplex CNN produced commendable results at 96.6% when tested on ALL-IDB2 dataset using 50% of the data for texting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning representations of multichannel data using higher dimension algebras has been proved to outperform real-valued approaches in several problems [6,7,8,9]. Quaternion-valued networks already boast works on a significant array of diverse tasks such as audio signal and image processing, computer vision, and dynamic system modeling [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%